Corrosion vs. fatigue in a high-strength steel specimen investigated via FEM - Malíková, Lucie; Benešová, Anna; Al Khazali, Mohammad Sami; Seitl, Stanislav (Elsevier, 2024)
The work is devoted to investigations of the stress distribution/concentration in a corroded specimen loaded via remote tensile loading. Existence of corrosion pits of various size and various mutual distance affects stress distribution in a specimen which can have influence on its lifetime. Thus, numerical simulations via finite element method were performed in order to assess the stress field near corrosion pits in specimens made of high-strength steel. The geometry of the numerical model was suggested based on the dimensions of the real specimens produced for fatigue experiments. The results obtained are discussed and mutual comparison with experimental data is intended in oncoming months.

The work is devoted to investigations of the stress distribution/concentration in a corroded specimen loaded via remote tensile loading. Existence of corrosion pits of various size and various mutual distance affects stress distribution in a specimen which can have influence on its lifetime. Thus, numerical simulations via finite element method were performed in order to assess the stress field near corrosion pits in specimens made of high-strength steel. The geometry of the numerical model was suggested based on the dimensions of the real specimens produced for fatigue experiments. The results obtained are discussed and mutual comparison with experimental data is intended in oncoming months.
Corrosion vs. fatigue in a high-strength steel specimen investigated via FEM
Keywords: High-strength steels; finite element analysis; corrosion pits; stress concentration; High-strength steels; finite element analysis; corrosion pits; stress concentration